Acute Aortic Regurgitation Due to Endocarditis Caused by Disseminated Gonococcal Infection: A Case Report. Issue 3 (24th March 2021) - Neto, Ana; Sevilha, Joana; Seabra, Daniel; Oliveira, Inês; Santos, Rui Pontes; Andrade, Aurora; Pinho, Paulo; Costa, Paula Martins; Viana, Mariana; Pinto, Paula
Abstract : A severe aortic regurgitation with large vegetation was found on a young patient. Blood cultures were positive for Neisseria gonorrhoeae . Despite direct antibiotherapy, the patient required valve replacement surgery. Abstract: A 23-year-old man presented with cough and progressive shortness of breath. Echocardiogram showed a biscupid aortic valve with a large vegetation causing severe regurgitation. Blood cultures were positive for Neisseria gonorrhoeae sensitive to cefotaxime and penicillin. Despite direct antibiotherapy, the patient required cardiac surgery with aortic valve replacement.